Estudo da mecânica da danificação aplicada ao concreto contendo cinza de casca de arroz residual com auxílio da técnica de correlação digital de imagens - Rebouças, Emanuel Carvalho (Universidade Federal Rural do Semi-Árido, 2019)
The investigation of the mechanical degradation of concrete made with residual materials has been highlighting in the last decades, because to the importance that the use of alternative materials represents to promote the adequate management of the solid residues generated in the most different industrial processes in addition some, due to their characteristics , provide improvements in the mechanical properties of concretes, being relevant to verify if these are durable or not. Thus, this work has as objective to investigate the degradation process of the mechanical properties, under uniaxial compression, of the concrete containing residual rice husk ash (RHA), through a scalar Damage variable. The method used was that of the variation of the effective modulus of elasticity, using Digital Image Correlation technique. (CDI). Following the established experimental program, a grinding time of 120 minutes was chosen for the residual rice husk ash (RHA). Four concrete families were made, containing partial replacement, by mass, of Portland cement by grinded RHA, contents: 0% (reference), 10%, 15% and 20%. Were molded for each family of concrete, cubic specimens with edges of 10 cm, which were kept in humid curing for 91 days. Were made destructive testing of specimens in a simple uniaxial compression strength and compression strength with loading and unloading, using DIC technique, for measuring the strain along the mechanical tests. Was verified that the application of the DIC technique allowed an accurate measurement of the deformation fields formed on the surface of the concretes. Was also found that the use of grinded residual RHA as pozzolan in concretes proved to be a technically feasible option, especially in the substitution levels of 10% and 15%. Concretes containing RHA showed higher compression strength (α = 0.05); equivalent initial modulus of elasticity (p> 0.05) and a small reduction of damaging, compared to the reference concrete
Keywords: Concreto; Cinza da casca do arroz (CCA); Mecânica do Dano; Extensiometria Óptica; Concrete; Rice Husk Ash (RHA); Damage Mechanics; Optical Extensiometry; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA